Stem cell‐ and gene‐based therapies as potential candidates in Alzheimer's therapy. Issue 11 (3rd August 2018) - Hosseini, Seyede Atefe; Mohammadi, Rezvan; Noruzi, Somaye; Mohamadi, Yousef; Azizian, Mitra; Mousavy, Seyed Mojta; Ghasemi, Faezeh; Hesari, AmirReza; Sahebkar, Amirhossein; Salarinia, Reza; Aghdam, Arad Mobasher; Mirzaei, Hamed
Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder, which is associated with impairments of memory, thinking, language, and reasoning. Despite extensive research aiming at the treatment of AD, durable and complete remissions are rare. Hence, new therapeutic approaches are required. Among various therapeutic approaches, stem cells (ie, neural stem cells, mesenchymal stem cells, and embryonic stem cells) and delivery of protective genes such as encoding nerve growth factor, APOE, and glial cell–derived neurotrophic factor have generated promise in AD therapy. Here, we summarized a variety of effective therapeutic approaches (ie, stem cells, and genes) in AD therapy.